From e-government to efficient transport: investigating Romania’s digital leverage in logistics - Maxim CETULEAN; Alexia GRAMA; Gabriel Cristian DUMITRU (Theoretical and Applied Economics, 2025)

(untitled)
Romania’s digital governance landscape is drawn through a modernized transport and logistic system. This paper tries to find out how further development in e-government, especially in the fields of digital public services, electronic procurement, and administrative interoperability can be strategic enablers for better efficiency in transport and logistics performance in Romania. Though under strong EU-alignment pressure and having made significant investments in digital infrastructure, Romania struggles with highly-disparate data systems, regional disparities, and low levels of cross-sector coordination. This paper accesses the present situation and future prospects of Romania’s capability to leverage European digital strategies over its national strategies for transport policy alongside European performance benchmarks. The major focus was on how initiatives of public sector digitalization – such as e-customs, the digital freight corridor, integrated e-platforms – can streamline logistics flows decrease transaction costs improve the standing of Romania as a regional transit hub. Case examples and comparative indicators reflect the advances and lags in digital maturity, particularly along vital logistics corridors and in urban transport networks. It ends with targeted policy measures to enhance the digital alignment of government services with the transport stakeholders focusing on data interoperability, institutional collaboration, and EU funding absorption. This study will help Romania understand how to convert e-government advancements into real improvements in transport efficiency and sustainable logistics development.